Implementation of Church Tasks Based on Acts 2:41-47 among Church Activists at the Synod of the Jakarta Baptist Christian Church - Ming, David; Purnomo, Yonathan; Windarti , Maria Titik; Andrian, Tonny; Suksmono, Ari (Technium Social Sciences Journal, 2023)
The early congregation became a pioneer as well as a barometer for today's churches in the Implementation of Church Tasks. The early congregation carried out 4 (four) Church tasks correctly and in a balanced manner; 1. Teaching God's Word, 2. Fellowship, 3. Service of Love and 4. Witnessing. The early congregation did all this sincerely, bravely with a burning and constant spirit, the impact was a very rapid and significant increase in the number of souls. Today's churches must reflect on the early congregation in carrying out church life. The method used in this research is a quantitative method. The results of this conclusion can be seen from the results of calculations using Confidence Interval statistical calculations at a significance level of 5% resulting in Lower Bound and Upper Bound 225.5202 – 231.8353. Which is in the high interval or it can be said that the position of the Level of Implementation of Church Tasks based on Acts 2:41-47 among Church Activists at the Synod of the Jakarta Baptist Christian Church (Y) is in the high category.